Coloniality and Intersectionality in Social Work Education and Practice. Issue 2 (4th May 2019) - Almeida, Rhea V.; Werkmeister Rozas, Lisa Marie; Cross-Denny, Bronwyn; Lee, Karen Kyeunghae; Yamada, Ann-Marie
ABSTRACT: The history of social work education is deeply entangled with the structures of White supremacy and coloniality. Through an analysis of coloniality, the system from which social work operates, this article outlines an alternative framework of intersectionality, which decodes the dominant discourse in relation to power, privilege, White supremacy, and gender oppression. The framework of intersectionality moves professional social work pedagogy and practice from the trenches of coloniality toward decoloniality. The concepts of intersectionality and critical consciousness are operationalized to demonstrate how social work education can effect structural and transformational change through de-linking from its white supremacists roots.